2015
DOI: 10.2105/ajph.2015.302710
|View full text |Cite
|
Sign up to set email alerts
|

Sharing a Playbook: Integrated Care in Community Health Centers in the United States

Abstract: A 2-pronged strategy involving financial incentives and technical assistance to spread best practices might increase integrated care, particularly among health centers that are not maximizing the potential of electronic health records and health centers with low behavioral health staffing levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Overall, eight studies identified barriers to coordinated care 18 25 ( Table 1 ), and 13 studies 9 , 12 , 16 , 26 – 35 ( Table 2 ) did not specifically mention challenges facing care coordination, five of which 9 , 12 , 18 , 34 , 35 were specifically designed to compare the collaborative care model to CAU ( Table 2 ). Mental health illnesses addressed in the reviewed articles included dementia (n=2), 18 , 27 suicide (n=1), 28 substance abuse (n=4), 22 , 24 , 28 , 31 posttraumatic stress disorder (PTSD; n=2), 32 , 33 schizophrenia (n=1), 32 anxiety (n=1), 35 and depression, the most prevalent mental health condition assessed for collaborative care (n=9). 9 , 12 , 18 , 20 , 26 28 , 34 , 35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, eight studies identified barriers to coordinated care 18 25 ( Table 1 ), and 13 studies 9 , 12 , 16 , 26 – 35 ( Table 2 ) did not specifically mention challenges facing care coordination, five of which 9 , 12 , 18 , 34 , 35 were specifically designed to compare the collaborative care model to CAU ( Table 2 ). Mental health illnesses addressed in the reviewed articles included dementia (n=2), 18 , 27 suicide (n=1), 28 substance abuse (n=4), 22 , 24 , 28 , 31 posttraumatic stress disorder (PTSD; n=2), 32 , 33 schizophrenia (n=1), 32 anxiety (n=1), 35 and depression, the most prevalent mental health condition assessed for collaborative care (n=9). 9 , 12 , 18 , 20 , 26 28 , 34 , 35…”
Section: Resultsmentioning
confidence: 99%
“…A variety of health care centers were used to assist collaborative care efforts. The majority of care coordination took place within primary care centers (n=8),9,19,22,25,28,31,34,35 followed by community health centers (n=4), 19 , 21 , 22 , 31 the veterans integrated health care system (n=5), 12 , 26 , 30 , 32 , 33 the correctional health system, 29 and independent living facilities. 27 Seven studies examined coordinated care in rural areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should explore the barriers to on‐site provision of substance use disorder services in health centers such as the patient cap for DEA‐waivered prescribers, with a focus on barriers in rural areas . The integration of behavioral health and medical services should be a focus area for future research, since integrated services are more likely to address patient needs in a comprehensive and high‐quality way . One previous study highlights the link between buprenorphine maintenance and increased access to preventive care, which should be further explored .…”
Section: Discussionmentioning
confidence: 99%
“…10,47 The integration of behavioral health and medical services should be a focus area for future research, since integrated services are more likely to address patient needs in a comprehensive and high-quality way. 48 One previous study highlights the link between buprenorphine maintenance and increased access to preventive care, which should be further explored. 49 Future research should also further explore community partnerships 50 and primary care as an effective distribution hub for naloxone, which is an antidote that can reverse opioid overdoses if administered in time.…”
Section: Discussionmentioning
confidence: 99%